Ceramic sheet blank, ceramic sheet and preparation method of ceramic sheet blank
By combining modified kaolin and plant fibers, a reinforcement network is formed, which solves the problem of insufficient strength and toughness of ceramic sheets, significantly improves its bending, compressive and toughness properties, and reduces the risk and cost of transportation damage.
Patent Information
- Application Number
- CN202411852660.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
Due to insufficient strength and toughness, existing ceramic thin plates are easily damaged during transportation and use, which increases transportation costs.
Modified kaolin, quartz sand, feldspar powder, diatomaceous earth, modified plant fibers, calcium carbonate, barium sulfate, sodium silicate, thickener, stabilizer and titanium dioxide are used to form a strengthening network through the modification of zirconia and silicon hydride, and the strength and toughness of the blank are improved, and the plant fibers are modified by phthalate coupling agents to enhance their dispersion and binding strength in the blank.
It significantly improves the bending strength, compressive strength and toughness of ceramic sheets, reduces the risk of transportation damage, reduces transportation costs, and makes the blank easier to form when pressed, and has a more uniform and flat surface.
Smart Images

Figure BDA0005190989980000081 
Figure BDA0005190989980000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic technology, and more specifically, to a ceramic thin plate blank, a ceramic thin plate and a preparation method thereof. Background Art
[0002] Ceramic materials are widely used in construction, decoration and daily necessities due to their unique physical and chemical properties. As the basis of ceramic products, the quality of ceramic green bodies directly affects the performance and appearance of the final products. Therefore, improving the quality of ceramic green bodies has always been the research focus in the field of ceramic manufacturing.
[0003] In the prior art, the ceramic thin plate is thin and has a large area, resulting in insufficient strength and toughness. As a result, once a bump occurs during transportation and use, the ceramic thin plate will be damaged, increasing its transportation cost. Summary of the invention
[0004] The purpose of the present invention is to solve the problems existing in the prior art and to provide a ceramic thin plate blank, a ceramic thin plate and a preparation method thereof with high strength and toughness.
[0005] One of the present inventions is to provide a ceramic thin plate blank, comprising 25-35 parts of modified kaolin, 20-25 parts of quartz sand, 10-20 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer, and 1-3 parts of titanium dioxide.
[0006] Further, it includes 30-34 parts of modified kaolin, 22-24 parts of quartz sand, 15-17 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer, and 1-3 parts of titanium dioxide.
[0007] When the green body formula ratio is 34 parts of modified kaolin, 22-24 parts of quartz sand, and 15-17 parts of feldspar powder, the strength and toughness of the green body are better.
[0008] Further, the treatment of kaolin comprises the following steps:
[0009] A1. Wash and select kaolin and crush it;
[0010] A2. Sieve the crushed kaolin;
[0011] A3. Mix the sieved kaolin with the modifier, crush and sieve again after mixing.
[0012] Further, 4-6% zirconium oxide and 2-4% silicon hydride are added per part of kaolin.
[0013] Furthermore, the crushed kaolin and the modifier are mixed and reacted in a drying device, and the device temperature is 80-150°C.
[0014] In the present invention, zirconium oxide can improve the strength and toughness of the blank, while silicon hydride helps to improve the hardness and wear resistance of the blank. The combination of the two as a modifier combined with kaolin can form a reinforcement network, which can further improve the toughness of the blank, ensure its structural strength, and reduce the loss generated during transportation. At the same time, the reinforcement grid formed by the modifier can increase the direct involvement of kaolin and plant fibers, which can further improve the toughness and connection strength of the blank, improve its bending strength and compressive strength, and reduce cracking. On the other hand, the modified kaolin can also enhance its bonding with other components in the blank, thereby improving the overall strength and toughness of the blank, and because it has good plasticity and fluidity, it can make the blank easier to shape during pressing, making the surface of the blank more uniform and smooth.
[0015] Furthermore, the treatment of the modified plant fiber comprises the following steps:
[0016] B1. Screen plant fibers to remove impurities and coarse fibers;
[0017] B2. Refine the plant fibers;
[0018] B3. Use titanate coupling agents to modify plant fibers;
[0019] B4. Pre-treat the modified plant fiber and control its humidity to 60-75% for standby use.
[0020] Furthermore, the amount of coupling agent added is 1-3% of the mass of the plant fiber.
[0021] Plant fibers themselves have good elasticity and flexibility, and can absorb and disperse external forces. Therefore, after the green body is formed, the plant fibers are intertwined with each other, which improves the bending strength and impact resistance of the green body, making the ceramics less likely to break. In addition, by cutting and rolling the plant fibers, the dispersion and bonding strength in the green body can be improved, which can improve the toughness of the ceramics; by controlling its humidity, it can be better mixed with other materials in the green body, and it has high fluidity and can be evenly distributed, making the green body easier to form, reducing defects and improving the quality of product forming; coupling agents can improve the compatibility of plant fibers with other green body components such as kaolin and quartz sand, so that the plant fibers can be better dispersed in the green body material, and the chemical bonding between the plant fibers and other components of the green body is enhanced, further improving the toughness and flexural strength of the green body.
[0022] Furthermore, the feldspar powder is a mixture of potassium feldspar and sodium feldspar in a ratio of one to one.
[0023] A second object of the present invention is to provide a ceramic thin plate made from the above-mentioned ceramic thin plate blank.
[0024] A third object of the present invention is to provide a method for preparing the ceramic thin plate, comprising the following steps:
[0025] S1, mixing the raw materials according to specific gravity and pressing them into blanks;
[0026] S2, drying the green body;
[0027] S3, applying a base glaze on the dried body and inkjet printing, and spraying a protective glaze after drying again;
[0028] S4, placing the green body into a kiln for firing and forming;
[0029] S5. Polishing and edge grinding are performed on the fired ceramics.
[0030] During firing, thermal expansion and contraction will cause ceramics to deform to a certain extent, and plant fibers have a certain elastic deformation. Therefore, adding plant fibers allows the green body to be adaptively adjusted and the firing performance is optimized.
[0031] Furthermore, in step S2, the drying temperature is 140-150°C; in step S3, the specific gravity of the protective glaze is 1.20-1.30 g / mL, and the glaze application amount is 350-400 g / m 2 ; In step S4, the firing temperature of the kiln is 1198-1200°C and the firing time is 50-55min.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention utilizes zirconium oxide and silicon hydride to modify kaolin, which can enhance the mechanical strength of the blank, improve its bending strength and compressive strength, and zirconium oxide and silicon hydride can form a reinforcing grid to cooperate with plant fibers, increase the direct connection between kaolin and plant fibers, improve toughness and connection strength, and reduce cracking.
[0034] 2. The modified kaolin in the formula of the present invention has good plasticity and fluidity, which can make the green body easier to shape during pressing and make the surface of the green body more uniform and smooth.
[0035] 3. The present invention improves the dispersibility and bonding force of plant fibers in the green body by cutting and rolling them, thereby improving the toughness of ceramics; the plant fibers are modified by titanate coupling agents to increase their tensile properties, flexural strength and impact strength in the green body; the coupling agent can improve the compatibility of plant fibers with other green body components such as kaolin and quartz sand, so that the plant fibers can be better dispersed in the green body material, and the chemical bonding force between the plant fibers and other components of the green body is enhanced, further improving the toughness and flexural strength of the green body. DETAILED DESCRIPTION
[0036] The invention provides a ceramic thin plate blank, which comprises 25-35 parts of modified kaolin, 20-25 parts of quartz sand, 10-20 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer and 1-3 parts of titanium dioxide.
[0037] Preferably, in order to obtain better strength and toughness of the green body, the green body includes 34 parts of modified kaolin, 22-24 parts of quartz sand, 15-17 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer, and 1-3 parts of titanium dioxide.
[0038] In specific implementation, the treatment of kaolin includes the following steps:
[0039] A1. Wash and crush kaolin to achieve the required particle size;
[0040] A2. Screening the crushed kaolin through a screening device;
[0041] A3. The sieved kaolin is mixed with the modifier, crushed again after mixing, and sieved a second time through a screening device.
[0042] Preferably, 4-6% zirconium oxide and 2-4% silicon hydride are added to each portion of kaolin. When the amount of the modifier added is lower than this ratio, the strength, toughness, molding difficulty and uniformity of the green body produced are reduced, and when the amount of the modifier added is higher than this ratio, the strength, toughness and uniformity of the green body are not significantly increased, and the molding difficulty is greatly reduced.
[0043] Zirconia can improve the strength and toughness of the green body, while silicon hydride helps to improve the hardness and wear resistance of the green body. The combination of the two as a modifier combined with kaolin can form a reinforcement network, which can further improve the toughness of the green body, ensure its structural strength, and reduce the loss during transportation. At the same time, the reinforcement grid formed by the modifier can increase the direct connection between kaolin and plant fibers, which can further improve the toughness and connection strength of the green body, improve its bending strength and compressive strength, and reduce cracking. On the other hand, modified kaolin can enhance its bonding with other components in the green body, thereby improving the overall strength and toughness of the green body. And because it has good plasticity and fluidity, it can make the green body easier to shape during pressing, making the green body surface more uniform and smooth.
[0044] In specific implementation, the treatment of the modified plant fiber includes the following steps:
[0045] B1. Screen plant fibers to remove impurities and coarse fibers;
[0046] B2. Refine the plant fibers;
[0047] B3. Use titanate coupling agents to modify plant fibers;
[0048] B4. Pre-treat the modified plant fiber and control its humidity to 60-75% for standby use.
[0049] In the specific implementation, the coupling agent used is TMC-7 phthalate coupling agent produced by Tianchang Green Chemical Additive Factory.
[0050] Preferably, when the amount of coupling agent added is 1-3%, the compatibility of plant fibers with other blank components can be significantly improved, the fibers can be better dispersed in the blank material, the chemical bonding force between the plant fibers and other blank components can be enhanced, and the bending strength, compressive strength and impact strength of the blank can be improved; the coupling agent introduces ester groups on the fiber surface through chemical reaction, thereby improving the hydrophobicity and thermal stability of the fiber, thereby optimizing the overall performance of the blank.
[0051] When the amount of coupling agent added is less than 1%, the compatibility of plant fiber with other components can be partially improved, but the effect on improving the performance of the green body is limited.
[0052] When the amount of coupling agent added is less than 3%, the plant fiber is over-modified, which will cause unevenness in the internal structure of the green body, resulting in uneven distribution of strength and toughness, and affecting other properties of the green body, such as air permeability; and excessive use of coupling agent will increase costs without bringing significant improvements in performance.
[0053] Plant fibers themselves have good elasticity and flexibility, and can absorb and disperse external forces. Therefore, after the green body is formed, the plant fibers are intertwined with each other, which improves the bending strength and impact resistance of the green body, making the ceramics less likely to break. In addition, by cutting and rolling the plant fibers, the dispersion and bonding strength in the green body can be improved, which can improve the toughness of the ceramics; by controlling its humidity, it can be better mixed with other materials in the green body, and it has high fluidity and can be evenly distributed, making the green body easier to form, reducing defects and improving the quality of product forming; coupling agents can improve the compatibility of plant fibers with other green body components such as kaolin and quartz sand, so that the plant fibers can be better dispersed in the green body material, and the chemical bonding between the plant fibers and other components of the green body is enhanced, further improving the toughness and flexural strength of the green body.
[0054] In a specific implementation, the feldspar powder is a mixture of potassium feldspar and sodium feldspar in a ratio of one to one.
[0055] A third object of the present invention is to provide a method for preparing the ceramic thin plate, comprising the following steps:
[0056] S1, mixing the raw materials according to specific gravity and pressing them into blanks;
[0057] S2, drying the green body;
[0058] S3, applying a base glaze on the dried body and inkjet printing, and spraying a protective glaze after drying again;
[0059] S4, placing the green body into a kiln for firing and forming;
[0060] S5. Polishing and edge grinding are performed on the fired ceramics.
[0061] During firing, thermal expansion and contraction will cause ceramics to deform to a certain extent, and plant fibers have a certain elastic deformation. Therefore, adding plant fibers allows the green body to be adaptively adjusted and optimizes firing performance.
[0062] In the specific implementation, in step S2, the drying temperature is 140-150°C, in step S3, the specific gravity of the protective glaze is 1.20-1.30 g / mL, and the glaze amount is 350-400 g / m 2 In step S4, the firing temperature of the kiln is 1198-1200°C, and the firing time is 50-55 minutes.
[0063] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0064] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0065] Example 1
[0066] This embodiment provides a ceramic thin plate, and the specific preparation method is as follows:
[0067] (1) Kaolin modification
[0068] crushing the washed kaolin;
[0069] The crushed kaolin is passed through a 400 sieve by a screening device;
[0070] The sieved kaolin is mixed with 5% zirconium oxide and 3% silicon hydride per kaolin, and the mixture is put into a drying device at a temperature of 100° C. and stirred to be fully mixed;
[0071] The modified kaolin is crushed again and screened twice to 600 meshes through a screening device to evenly disperse the modifier.
[0072] (2) Plant fiber modification
[0073] Screening plant fibers to remove impurities and coarse fibers;
[0074] Plant fibers are refined by cutting and rolling;
[0075] 1.5% of phthalate coupling agent was added to modify the plant fiber;
[0076] The plant fibers are pre-treated and their humidity is controlled to 60% for later use.
[0077] (3) The treated kaolin, the treated plant fiber and other raw materials are mixed in a ratio of 30 parts of modified kaolin, 22 parts of quartz sand, 15 parts of feldspar powder, 8 parts of diatomaceous earth, 5 parts of modified plant fiber, 10 parts of calcium carbonate, 4 parts of barium sulfate, 3 parts of sodium silicate, 1 part of thickener, 1 part of stabilizer, and 1 part of titanium dioxide, and a slurry is prepared by a ball mill, and then a powder is prepared by a spray drying tower, and finally a green body is formed by a press.
[0078] (4) The body is dried, and then a base glaze is applied and inkjet printed, and then a protective glaze is sprayed after drying again; the base glaze formula used in this embodiment includes the following components in terms of weight percentage: 20.47% Al 2 O 3 、65.12%SiO 2 、1.16%Na 2 O, 1.6% K 2 O, 1.38% CaO, 0.10% TiO 2 、0.19%Fe 2 O 3 , 2.8% ZrO 2 、0.28%MgO、0.32%LiO 2 , 0.02% PbO, 1.29% ZnO, 0.02% MnO, 0.01% SrO, 0.01% Cr 2 O 3 , 0.1% B 2 O 3 、0.14%Rb 2 O, 0.1% Cs 2 O. The loss on ignition is 4.57%, and the remainder is impurities.
[0079] The process parameters of the base glaze slurry are as follows: the base glaze fineness is 0.5% of the mass of the residue after sieving through 325 mesh, and the specific gravity of the base glaze slurry is 1.8g / cm 3 The glaze amount of the bottom glaze in this embodiment is 400g / m 2 .
[0080] (5) The green body is placed in a kiln and fired at 1198° C. for 50 min to form a green body. After firing, the green body is polished and edge-grinded.
[0081] Example 2
[0082] This embodiment provides a ceramic thin plate, and the specific preparation method is as follows:
[0083] (1) Kaolin modification
[0084] crushing the washed kaolin;
[0085] The crushed kaolin is passed through a 400 sieve by a screening device;
[0086] The sieved kaolin is mixed with 4% zirconium oxide and 2% silicon hydride per kaolin, and the mixture is put into a drying device at a temperature of 150° C. and stirred to be fully mixed;
[0087] The modified kaolin is crushed again and screened twice to 600 meshes through a screening device to evenly disperse the modifier.
[0088] (2) Plant fiber modification
[0089] Screening plant fibers to remove impurities and coarse fibers;
[0090] Plant fibers are refined by cutting and rolling;
[0091] Add 2% phthalate coupling agent to modify the plant fiber;
[0092] The plant fibers are pre-treated and their humidity is controlled to 70% for later use.
[0093] (3) The treated kaolin, the treated plant fiber and other raw materials are mixed in a ratio of 34 parts of modified kaolin, 23 parts of quartz sand, 16 parts of feldspar powder, 10 parts of diatomaceous earth, 7 parts of modified plant fiber, 9 parts of calcium carbonate, 54 parts of barium sulfate, 5 parts of sodium silicate, 1 part of thickener, 2 parts of stabilizer, and 1 part of titanium dioxide, and a slurry is prepared by a ball mill, and then a powder is prepared by a spray drying tower, and finally a green body is formed by a press.
[0094] (4) The body is dried, and then a base glaze is applied and inkjet printed, and then a protective glaze is sprayed after drying again; the base glaze formula used in this embodiment includes the following components in terms of weight percentage: 20.47% Al 2 O 3 、65.12%SiO 2 、1.16%Na 2 O, 1.6% K 2 O, 1.38% CaO, 0.10% TiO 2 、0.19%Fe 2 O 3 , 2.8% ZrO 2 、0.28%MgO、0.32%LiO 2 , 0.02% PbO, 1.29% ZnO, 0.02% MnO, 0.01% SrO, 0.01% Cr 2 O 3 , 0.1% B 2 O 3 、0.14%Rb 2 O, 0.1% Cs 2 O. The loss on ignition is 4.57%, and the remainder is impurities.
[0095] The process parameters of the base glaze slurry are as follows: the base glaze fineness is 0.5% of the mass of the residue after sieving through 325 mesh, and the specific gravity of the base glaze slurry is 1.8g / cm3 ; And the glaze amount of the bottom glaze in this embodiment is 350g / m 2 .
[0096] (5) The green body is placed in a kiln and fired at 1198° C. for 50 min to form a green body. After firing, the green body is polished and edge-grinded.
[0097] Comparative Example
[0098] Comparative Example 1 is compared with Example 1, and the only difference is that the kaolin is not modified.
[0099] Comparative Example 2 is compared with Example 1, and the only difference is that the ratio of the modifier is 3% zirconium oxide and 1% silicon hydride.
[0100] Comparative Example 3 is compared with Example 1, and the only difference is that the ratio of the modifier is 7% zirconium oxide and 5% silicon hydride.
[0101] Comparative Example 4 is compared with Example 2, and the only difference is that the plant fiber is not modified.
[0102] Comparative Example 5 is compared with Example 2, and the only difference is that the concentration of the coupling agent is 0.5%.
[0103] Comparative Example 6 is compared with Example 2, and the only difference is that the concentration of the coupling agent is 4%.
[0104] Comparative Example 7 is compared with Example 2, and the only difference is that no plant fiber is added.
[0105] Test Example 1
[0106] The ceramics obtained in Examples 1-2 and Comparative Examples 1-6 were tested for green body strength, toughness and ease of forming, and the test results were as follows:
[0107] Table 1
[0108]
[0109] The scoring criteria for molding difficulty are as follows:
[0110] 10 points: The molding process is very easy, the green body has excellent fluidity, good stability, and easy demoulding without any additional operation.
[0111] 8-9 points: The molding process is relatively easy, the green body has good fluidity, good stability, and demolding is relatively easy.
[0112] 6-7 points: The molding process is somewhat difficult, the fluidity of the blank is average, the stability is acceptable, and demolding requires certain skills.
[0113] Below 6 points: The molding process is difficult, the fluidity of the blank is poor, the stability is average, and demolding is difficult, which may require multiple attempts.
[0114] The scoring criteria for green body uniformity are as follows:
[0115] 10 points: The body is completely uniform, without any visible defects such as color difference, pores, cracks or impurities, the microstructure is consistent, and the physical and chemical properties remain constant throughout the body.
[0116] 8-9 points: The blank is very uniform and almost defect-free, or the defects are very small and do not affect the overall performance of the blank. At the microscopic level, the structure is almost completely consistent.
[0117] 6-7 points: The body is relatively uniform, with some minor defects, such as small color difference or a small amount of pores, but these defects do not significantly affect the overall performance of the body, and the microstructure is basically consistent.
[0118] Below 6 points: The uniformity of the green body is average, with obvious defects such as color difference, pores or cracks. These defects may have a certain impact on certain properties of the green body, and there is a certain inconsistency in the microstructure.
[0119] According to the test results, compared with Example 1, Comparative Example 1 did not modify the kaolin, and the ceramic body strength, toughness, molding difficulty and body uniformity of Comparative Example 1 were all lower than the ceramic produced in Example 1, which proves that the ceramic produced by the present invention has better body strength and toughness than the ceramic without modified kaolin.
[0120] Compared with Example 1, Comparative Example 2-3 uses 3 parts of zirconium oxide and 1 part of silicon hydride to modify kaolin in Comparative Example 2, which is lower than the proportion of the modifier specified in the present invention. The measured green body strength in Comparative Example 2 is 35.5, toughness is 4.7, molding difficulty is 8.7, and green body uniformity is 9.0, all of which are less than the data in Example 1, indicating that a modifier ratio lower than the ratio specified in the present invention will result in a decrease in the strength, toughness and uniformity of the obtained green body; Comparative Example 3 uses 7% zirconium oxide and 5% silicon hydride to modify kaolin, which is higher than the proportion of the modifier specified in the present invention. The green body strength, toughness and green body uniformity measured in Comparative Example 3 are not much different from those in the embodiment, but the molding difficulty is increased, indicating that a modifier ratio higher than the ratio specified in the present invention will increase the molding difficulty of the obtained green body.
[0121] Compared with Example 2, Example 4 does not modify the plant fiber. The ceramic body strength, toughness and molding difficulty of Example 4 are all lower than those of the ceramic prepared in Example 2, which proves that the ceramic prepared by the present invention has better body strength and toughness and is easier to mold than the ceramic without modifying the kaolin.
[0122] Comparative Examples 5-6 Compared with Example 2, in Comparative Example 5, a coupling agent with a concentration of 0.5% is used to modify the plant fiber, which is lower than the concentration of the coupling agent specified in the present invention. The green body strength, toughness, and molding difficulty of Comparative Example 5 are 35.5, 5.5, and 8.0, which are all lower than the data of Example 2, indicating that a coupling agent concentration lower than the ratio specified in the present invention will result in a decrease in the strength, toughness, and molding difficulty of the green body;
[0123] In Comparative Example 6, a coupling agent with a concentration of 4% is used to modify the plant fiber, which is higher than the concentration of the coupling agent specified in the present invention. The strength and toughness of the blank in Comparative Example 6 are not much different from the data of Example 2, but the molding difficulty is much greater than that of Example 2, indicating that a coupling agent concentration higher than the proportion specified in the present invention will increase the molding difficulty of the blank and reduce the uniformity of the blank.
[0124] Compared with Example 2, Example 7 does not add plant fiber. The ceramic body strength, toughness and molding difficulty of Example 7 are all lower than the ceramic produced in Example 2, which proves that the ceramic produced by the present invention has better body strength and toughness and is easier to mold than the ceramic without modifying kaolin.
[0125] In summary, treating kaolin with a modifier can improve the toughness and overall strength of the green body. The modified kaolin has good plasticity and fluidity, which can make the green body easier to shape during pressing, and makes the green body surface more uniform and smooth. When the ratio of the added modifier is 4-6% zirconium oxide and 2-4% silicon hydride, the obtained ceramic green body has the best strength, toughness molding, difficulty and green body uniformity. Modifying plant fibers with phthalate coupling agents can improve the compatibility of plant fibers with other green body components, further improve the toughness and flexural strength of the green body, and when the amount of coupling agent used is 1-3%, the obtained ceramic green body has the best strength, toughness molding, difficulty and green body uniformity.
[0126] Test Example 2
[0127] The three components of kaolin, quartz sand and feldspar powder were modified in Example 1, and the green body strength, toughness and molding difficulty of the ceramic thin plate obtained were tested, and the experimental data were obtained as shown in Table 2 below:
[0128] Table 2
[0129]
[0130] From the data in Table 2, it can be seen that considering the four properties of green body strength, toughness, molding difficulty and green body uniformity, the comprehensive performance of experimental bodies 6 and 9 is the best. The proportion of experimental body 6 is 34 parts of modified kaolin, 24 parts of quartz sand, and 15 parts of feldspar powder, and the proportion of experimental body 9 is 34 parts of modified kaolin, 22 parts of quartz sand, and 17 parts of feldspar powder.
[0131] Therefore, when the ratio of kaolin, quartz sand and feldspar powder in the green body is 34 parts of modified kaolin, 22-24 parts of quartz sand and 15-17 parts of feldspar powder, the strength and toughness of the green body are better.
[0132] The present invention utilizes zirconium oxide and silicon hydride to process kaolin, wherein zirconium oxide improves the strength and toughness of a blank, and silicon hydride improves the hardness and wear resistance of the blank. The combination of the two as a modifier combined with kaolin can form a reinforcing network, which can further improve the toughness of the blank. The modified kaolin has good plasticity and fluidity, which can make the blank easier to shape during pressing, and make the surface of the blank more uniform and smooth. The coupling agent is used to modify the plant fiber, which can improve the compatibility of the plant fiber with other blank components such as kaolin and quartz sand, so that the plant fiber can be better dispersed in the blank material, so that the chemical bonding force between the plant fiber and other blank components is enhanced, and the toughness and flexural strength of the blank are further improved.
[0133] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A ceramic thin plate body, characterized in that: It includes 25-35 parts of modified kaolin, 20-25 parts of quartz sand, 10-20 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer and 1-3 parts of titanium dioxide.
2. A ceramic thin plate body according to claim 1, characterized in that: It includes 34 parts of modified kaolin, 22-24 parts of quartz sand, 15-17 parts of feldspar powder, 8-12 parts of diatomaceous earth, 5-8 parts of modified plant fiber, 8-12 parts of calcium carbonate, 3-6 parts of barium sulfate, 3-6 parts of sodium silicate, 1-2 parts of thickener, 1-2 parts of stabilizer and 1-3 parts of titanium dioxide.
3. A ceramic thin plate body according to claim 1, characterized in that: The treatment of the modified kaolin comprises the following steps: A1. Wash and select kaolin and crush it; A2. Sieve the crushed kaolin; A3. Mix the sieved kaolin with the modifier, crush and sieve again after mixing.
4. A ceramic thin plate body according to claim 3, characterized in that: In step A3, 4-6% zirconium oxide and 2-4% silicon hydride are added to each part of kaolin.
5. The ceramic thin plate body according to claim 3, characterized in that: In step A3, the crushed kaolin and the modifier are mixed and reacted in a drying device at a temperature of 80-150°C.
6. The ceramic thin plate body according to claim 1, characterized in that: The treatment of the modified plant fiber comprises the following steps: B1. Screen plant fibers to remove impurities and coarse fibers; B2. Refine the plant fibers; B3. Use titanate coupling agents to modify plant fibers; B4. Pre-treat the modified plant fiber and control its humidity to 60-75% for standby use.
7. The ceramic thin plate green body according to claim 6, characterized in that: In step B3, the amount of coupling agent added is 1-3% of the mass of the plant fiber.
8. A ceramic thin plate, characterized in that: The ceramic thin plate blank is made by using the ceramic thin plate blank according to any one of claims 1 to 7.
9. A method for preparing the ceramic thin plate as claimed in claim 8, characterized in that: The following steps are involved: S1, mixing the raw materials according to proportion and pressing them into blanks; S2, drying the green body; S3, applying a base glaze on the dried body and inkjet printing, and spraying a protective glaze after drying again; S4, placing the green body into a kiln for firing and forming; S5. Polishing and edge grinding are performed on the fired ceramics.
10. The method for preparing a ceramic thin plate according to claim 9, characterized in that: In step S2, the drying temperature is 140-150°C; and / or, in step S3, the specific gravity of the applied protective glaze is 1.20-1.30 g / mL, and the glaze amount is 350-400 g / m 2 ; and / or, in step S4, the firing temperature of the kiln is 1198-1200°C and the firing time is 50-55min.
Citation Information
Cited By
Functional ceramic blank and preparation method thereof
CN120398569A